The lncRNA landscape of breast cancer reveals a role for DSCAM-AS1 in breast cancer progression - Yashar S. Niknafs (Nature Portfolio, 2016)
LncRNAs have been associated with cancer. Here, the authors carry out a systematic review of lncRNAs in breast cancer and show that DSCAM-AS1is highly expressed in oestrogen receptor positive tumours and enhances cancer through an interaction with hnRNPL; and is also associated with tamoxifen resistance.